2001
DOI: 10.1093/oxfordjournals.jbchem.a002859
|View full text |Cite
|
Sign up to set email alerts
|

Leupeptin-Induced Appearance of Partial Fragment of Betaine Homocysteine Methyltransferase during Autophagic Maturation in Rat Hepatocytes

Abstract: A cytosolic enzyme, betaine homocysteine methyltransferase (BHMT), and its partial fragments were discovered as autolysosomal membrane proteins from rat liver in the presence of leupeptin [Ueno et al. (1999) J. Biol. Chem. 274, 15222-15229]. The present study was undertaken to further characterize the transport and processing of BHMT from cytosol to autolysosome and to test if the fragment can be used as an in vitro probe for the maturation step of macroautophagy. Upon subcellular fractionation, BHMT (p44) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…85 BHMT fragments of ∼32 (p32) and ∼35 kDa (p35) were previously shown to accumulate in mitochondrial-lysosomal (ML) subcellular fractions and autolysosomes from rat hepatocytes treated with leupeptin, an inhibitor of intralysosomal protein degradation. 86,87 Whereas p32 appeared to be generated intralysosomally from autophagocytosed BHMT, 87 p35 was associated with autolysosomal membranes 86 and might perhaps be related to the autophagosomal membrane-associated BHMT fragments found in the present study. Both p32 and larger BHMT fragments could be generated proteolytically in liver cell extracts, 86,87 but how BHMT is processed in intact cells is not known.…”
Section: Table 3 Sequence Alignment Of Comt Peptides Identified By Mamentioning
confidence: 59%
“…85 BHMT fragments of ∼32 (p32) and ∼35 kDa (p35) were previously shown to accumulate in mitochondrial-lysosomal (ML) subcellular fractions and autolysosomes from rat hepatocytes treated with leupeptin, an inhibitor of intralysosomal protein degradation. 86,87 Whereas p32 appeared to be generated intralysosomally from autophagocytosed BHMT, 87 p35 was associated with autolysosomal membranes 86 and might perhaps be related to the autophagosomal membrane-associated BHMT fragments found in the present study. Both p32 and larger BHMT fragments could be generated proteolytically in liver cell extracts, 86,87 but how BHMT is processed in intact cells is not known.…”
Section: Table 3 Sequence Alignment Of Comt Peptides Identified By Mamentioning
confidence: 59%
“…Moreover, BHMT fragments (p32 and p35) have been found to accumulate in mitochondrial-lysosomal subcellular fractions and autolysosomes from rat hepatocytes treated with leupeptin, an inhibitor of intralysosomal protein degradation. 35,36) These observations and reports suggest that TG is involved in the formation of autophagosome and/ or autolysosome.…”
Section: Discussionmentioning
confidence: 80%
“…However, 3-methyladenine inhibits not only Class III PI-3K but also Class I kinase, and the concentration required for effective inhibition is very high. Treatment with inhibitors such as leupeptin, a cathepsin inhibitor, induces the formation of many vacuoles containing various cytoplasmic enzymes by blocking degradation in the lysosome, and biochemical analysis revealed that these represent non-selective enwrapping of cytosolic enzymes [24].…”
Section: Before the Autophagy-related Genesmentioning
confidence: 99%